Electoral Margins and American Foreign Policy1. Issue 3 (29th January 2013) - Potter, Philip B. K.
Abstract : Potter, Philip B. K. (2013) Electoral Margins and American Foreign Policy. International Studies Quarterly, doi: 10.1111/isqu.12040 © 2013 International Studies Association Conventional wisdom holds that large margins of electoral victory contribute to presidential power. How does this variation in power impact U.S. foreign policy? I argue here that presidents who win elections by a substantial margin authorize the use of substantial military force more regularly, but do so at the expense of personal diplomacy and low‐level crisis engagement. This distinction stems from the variation in the external constraint that other political actors place on these policies. New presidents who are empowered by a decisive election have more leverage and are therefore better able to pursue otherwise constrained foreign policies such as the use of major force. In contrast, those who win by smaller margins have less political capital and are forced disproportionately to the less constrained arenas of diplomacy and crisis intervention.